SLPW: A Virulent Bacteriophage Targeting Methicillin-Resistant Staphylococcus aureus In vitro and In vivo - Wang, Zhaofei; Zheng, Panpan; Ji, Wenhui; Fu, Qiang; Wang, Hengan; Yan, Yaxian; Sun, Jianhe (Frontiers in Microbiology, 2016)
Staphylococcus aureus (S. aureus) is a Gram-positive pathogen causing a variety of infections in humans and animals. Extensive use of antibiotics has led to the emergence of methicillin-resistant S. aureus (MRSA). As an alternative antibacterial agent against drug-resistant S. aureus, a lytic phage, designated SLPW, was isolated from fecal sewage in a pig farm. The SLPW was morphologically classified under Podoviridae and contains a double-stranded DNA genome. The genome of SLPW was 17861 bp (29.35% G+C) containing 20 open reading frames and lacked regions encoding lysogeny-related integrase gene and cI repressor gene. Phage SLPW showed a broad host range and high efficiency of plating against various types of S. aureus. One-step growth curve showed a short latency period (10 min) and a long lytic period (120 min). Phage SLPW remained stable under a wide range of temperatures or pH and was almost unaffected in chloroform or ultraviolet light. Further, it efficiently lysed MRSA strains in vitro and in vivo. Intraperitoneal phage administration at 1 h post-infection cured the mice and reduced the bacterial expression of inflammatory cytokines in mice. Specifically, the phage SLPW displayed a wide antibacterial spectrum. It was therapeutically effective against intra-abdominal infection in mice harboring different multilocus sequence typing (MLST) types of S. aureus strains. Therefore, phage SLPW is a potential therapeutic agent against MRSA infections.